Criminal trajectories: a developmental perspective - Day, David M. (Psychology and crime, 2019)
Introduction: criminal trajectories and life course development -- Theoretical backdrop -- Methodological approaches to modeling criminal trajectories -- Debates and controversies -- Developmental and life course models of crime -- Findings on the number and shape of criminal trajectories -- Predictors and correlates of criminal trajectory groups -- Later life outcomes, turning points, and desistance -- Implications for policy and practice -- Conclusion